Synthesis and Structural Characterization of Nanomanganese Ferrites - S.S. Yattinahalli; S.B. Kapatkar; S.N. Mathad (Журнал нано- та електронної фізики)
In this paper, the structural properties of nano manganese ferrite are synthesized by using environmental friendly co-precipitation method is reported. The structural parameters such as the lattice constant, average crystallite size (D), texture coefficients (TC), lattice strain (ε) and dislocation density (ρ) have been determined using X-ray diffraction data.